THE EFFECT OF GREEN ORGANIZATIONAL CLIMATE AND GREEN MOTIVATION ON EMPLOYEE GREEN BEHAVIOUR OF COMPANY THROUGH PERCEIVED ORGANIZATIONAL SUPPORT AS AN INTERVENING VARIABLE - Adelia Avita Aprilina; Dewi Andriani; Rifdah Abadiyah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the direct and indirect effects of Green Organizational Climate (GOC) and Green Motivation (GM) on Employee Green Behaviour (EGB), with Perceived Organizational Support (POS) as a mediator. Method: Using SEM with SmartPLS, findings show that GOC significantly increases POS but does not directly affect EGB; instead, its effect occurs through POS. Results: GM significantly influences EGB directly but not via POS. POS itself strongly predicts EGB, explaining 39.8% of its variance. Novelty: The study highlights POS as a central determinant of EGB, underscoring that green climates must be accompanied by tangible organizational support to foster sustainable employee behaviour.